HYDROLOGICAL ANALYSIS OF EACH LAND USE IN THE JOMPI RIVER WATERSHED, MUNA REGENCY - Zainun, Mariana; Yasin, Asramid; Hasani, Umar Ode; Sudia, La Baco; Fauzi, La Ode Muhammad Rizal (PT. Hafasy Dwi Nawasena, 2025)
This study analyzes the variation of infiltration rates across different land-use types in the upper watershed of the Jompi River Basin, Muna Regency, as an effort to understand hydrological responses to land-use change. Forest ecosystems play a crucial role in regulating water balance through enhanced soil porosity and organic matter accumulation, whereas land conversion often reduces infiltration capacity and increases surface runoff. Using a quantitative cross-sectional design, field measurements were conducted from August to October 2023 on four dominant land-use categories forest, agriculture, plantation, and settlement. Infiltration was measured using a double ring infiltrometer, while soil physical properties were analyzed through laboratory testing. The results indicate substantial variation in infiltration rates: plantations recorded the highest average value at 24.23 cm/hour, followed by secondary forest at 22.38 cm/hour, settlements at 19.23 cm/hour, and agricultural land at 16.59 cm/hour. These differences are strongly influenced by soil texture, organic matter, and porosity conditions. The findings demonstrate that land-use changes significantly alter soil hydrological behavior, highlighting the need for sustainable watershed management strategies. Further research is recommended to incorporate additional soil parameters such as permeability and to employ alternative infiltration models and rainfall simulators for improved measurement accuracy